New spaces and forms of tourism in experience economy - Stasiak, Andrzej (Turyzm/Tourism, 2013)
One of the best known economic theories of the early 21st c. is Pine & Gilmore’s of the experience economy (1999). This is nothing new for the tourism industry which has always been selling emotions, dreams and memories involving travel. Recently, however, it has become much more important to provide professionally (consciously and purposefully) prepared tourism products, strongly marked with emotion1. Efforts to create original experiences for tourists include not only various modifications of traditional tourism packages, but also a search for new recreation spaces and new forms of tourism. The aim of this article is to review new tourism-recreational areas (e.g. military areas, new churches, so-called ‘destination centres’, along with ordinary and extreme experience spaces), as well as new forms of travel and recreation (e.g. creative, event, sports, culinary or extreme tourism). The analysis includes those phenomena which above all are currently gaining in popularity as part of the tourist experience triad (WŁODARCZYK 2013).